2022
DOI: 10.3389/fenrg.2022.1029113
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a smart energy meter using blockchain and Internet of Things: A step toward energy conservation

Abstract: The looming energy crisis is affecting every sector of the world. The dire need to conserve energy has compelled researchers to bring automation to the power sector. The conservation of energy is one of the biggest challenges Third-World countries are facing in general and in Europe due to the Russian–Ukrainian war. There is a need to introduce such systems that can prevent energy loss and let users buy and sell excessive electricity they have. In the field of power and electricity, the Internet of Things (IoT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…AI plays a significant technological role in smart grids, and its applications can boost and enhance the reliability and resilience of smart The application of blockchain in smart grids involves various-use cases, including smart energy metering, energy trading, and data aggregation. It offers a secure and resilient framework for smart grid security, protecting against cyberattacks and ensuring system integrity and confidentiality [64]. Additionally, the performance of blockchain technology in smart grids has been analyzed, with studies conducting performance analyses using Ethereum and Hyperledger Fabric-based implementations, demonstrating its viability and potential benefits [65].…”
Section: Artificial Intelligence and Virtual Power Plantsmentioning
confidence: 99%
“…AI plays a significant technological role in smart grids, and its applications can boost and enhance the reliability and resilience of smart The application of blockchain in smart grids involves various-use cases, including smart energy metering, energy trading, and data aggregation. It offers a secure and resilient framework for smart grid security, protecting against cyberattacks and ensuring system integrity and confidentiality [64]. Additionally, the performance of blockchain technology in smart grids has been analyzed, with studies conducting performance analyses using Ethereum and Hyperledger Fabric-based implementations, demonstrating its viability and potential benefits [65].…”
Section: Artificial Intelligence and Virtual Power Plantsmentioning
confidence: 99%
“…The electrical vehicle owner has a numerical folder for payment and utilizes digital currency with the help of a smart phone application. In that application, centralized energy trading of EVs by using blockchain technology initializes transactions with the help of a node in the chain holding a smart contract [60,61]. For this, DLT was employed for monetary operations; however, numerous Energies 2024, 17, 2135 9 of 17 studies found that this knowledge could be utilized to create structures beyond monetary ones and exchange multiple secure transactions [39].…”
Section: 55] Internet Of Energy (Ioe) Techniquementioning
confidence: 99%
“…Their research highlighted the importance of visualizing data in real-time to facilitate decision-making. Tahir et al [28] explored the applications of ESP8266 microcontrollers in IoT-based systems. Their work discussed the capabilities and advantages of ESP8266 in terms of low power consumption, Wi-Fi connectivity, and compatibility with various sensors.…”
Section: Early Researchmentioning
confidence: 99%